(3bGYOI eTQhYjI GdOdjd GdLfGFj (B:s (3OQGSI ebGQfI (B/s - (3MSjf, YGOd YHO GdHOjY BOes ((3GdbGgQI (B:s (3OGQ GdfgVI GdYQHjI,s, 2015)
(3jJfGhd cJGH (B((3bGYOI eTQhYjI GdOdjd GdLfGFj (B: (3OQGSI ebGQfI(B) (3hGdPj bGe HJCdjag (B((3OcJhQYGOd YHO GdHOjY BOe MSjf(B) (3aj MhGdj (B(903) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdCOdI GdLfGFjI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdbSe GdChd, GdHGH GdJegjOj (B: (3acQI GdTQYjI GdLfGFjI, GdHGH GdKGfj (B: (3CQcGf bGYOI eTQhYjI GdOdjd GdLfGFj, GdHGH GdKGdK (B: (3GdMOhO GdbGfhfjI dbGYOI eTQhYjI GdOdjd GdLfGFj, GdbSe GdKGfj, GdHGH GdChd (B: (3CKGQ bGYOI eTQhYjI GdOdjd GdLfGFj Ydi GdELQGAGJ GdeGSI HGdMQjGJ GdTNUjI(B... (3EdN(B. s
(3HHdjhLQGajI (B: (3UaMI (B796-867.s
Keywords: (3GdCOdI GdLfGFjIs; (3GdJMbjb GdLfGFjs; (3GdLQjeI hGdeLQehfs -- (3bhGfjf hJTQjYGJs; (3GdbJds -- (3bhGfjf hJTQjYGJs; (3GdOaGY Yf GdeJge (B((3ELQGAGJ LfGFjI(B)s; (3GdRfGs -- (3bhGfjf hJTQjYGJs; (3GdeMGce GdLfGFjIs; (3GdSQbIs -- (3bhGfjf hJTQjYGJs; (3GdEKHGJ GdLfGFjs; (3GdCOdI GdLfGFjI (B((3abg ESdGej(B)s; (3GdbGfhf GdLfGFjs